Analisis Inflasi Dan Pengaruhnya Terhadap Jumlah Pengangguran Terbuka Di Kota Kediri - Kukuh H; Rike Kusuma Wardhani; Heru Sutapa (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
One of the problems that each region has is unemployment. The higher number of unemployed will hinder the development of the region because it is an indication of the many factors of production that are unemployed due to the lack of spending on factors of production by business actors. In addition, a high unemployment rate will also result in an increase in the poverty rate which will cause various social problems, one of which is an increase in criminal acts. Meanwhile, inflation is an indicator in the macro economy in determining the economic stability of a region. Changes in inflation rates will result in dynamics in economic problems. The purpose of this research is to analyze the influence of the inflation rate on the open unemployment rate in Kediri City. The analytical method used in this study is linear regression analysis, the coefficient of determination and hypothesis testing using Eviews 12. The data used in this research are data on the inflation rate and open unemployment rate in Kediri City in 2001 – 2022. The results show that the inflation rate has an effect positive and significant to the open unemployment rate in the City of Kediri.